Value for Money (VfM) as a Tool for Evaluating Zakat Fund Management Effectiveness - Larasati, Novia Anggraeni; Samsuri, Ali; Zainuddin, Moch.; Zunaidi, Arif (Al-Muhasib: Journal of Islamic Accounting and Finance, 2022)
This research aims to measure the efficiency and effectiveness of zakat fund management by BAZNAS Sidoarjo Regency using the value-for-money method for two years, namely 2021 and 2022. The research method used is qualitative with a descriptive approach. The measurement results show that the efficiency level in managing zakat funds in 2021 was 56%, which decreased to 46% in 2022. Despite the decline, during these two years, the efficiency level can be categorized as efficient. Meanwhile, the level of effectiveness in managing zakat funds reached 100% results in each program implemented, indicating a balanced level of effectiveness. In conclusion, BAZNAS Sidoarjo Regency has succeeded in maintaining an efficient level of efficiency in managing zakat funds, while the level of effectiveness remains balanced. This research contributes to understanding and improving the optimal management of zakat funds.